2011
DOI: 10.1063/1.3587103
|View full text |Cite
|
Sign up to set email alerts
|

Communication: A simple method for simulation of freezing transitions

Abstract: Despite recent advances, precise simulation of freezing transitions continues to be a challenging task. In this work, a simulation method for fluid-solid transitions is developed. The method is based on a modification of the constrained cell model which was proposed by Hoover and Ree [J. Chem. Phys. 47, 4873 (1967)]10.1063/1.1701730. In the constrained cell model, each particle is confined in a single Wigner-Seitz cell. Hoover and Ree pointed out that the fluid and solid phases can be linked together by adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
44
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 37 publications
(44 reference statements)
1
44
0
Order By: Relevance
“…The details of these simulations have been discussed in previous work. [5][6][7][8][9] As is evident in Fig. 1, at very low densities and pressures, the system behaves as an ideal gas, i.e., p* ∼ = ρ.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The details of these simulations have been discussed in previous work. [5][6][7][8][9] As is evident in Fig. 1, at very low densities and pressures, the system behaves as an ideal gas, i.e., p* ∼ = ρ.…”
mentioning
confidence: 86%
“…Similar mechanical stability points have also been seen in constant-volume simulations of soft-sphere and Lennard-Jones systems. 3,4 Recently, Nayhouse et al [5][6][7][8][9] proposed a simulation method for liquid-solid transitions which is based on constant-pressure simulations of generalized cell models. They found that the mechanical stability point of the solid phase, as modeled through the constrained cell model, appears in the form of an inflection point at about the same density and pressure as in previous work.…”
mentioning
confidence: 99%
“…As already commented, sizedependence issues can formally be resolved through finitesize scaling analysis for first-order phase transitions. [1][2][3] This task is, however, computationally demanding due to the substantial density range (from the low-ρ ideal-gas to the high-ρ incompressible regime) that must be sampled in a single simulation. Regarding system-size effects, previous work [3][4][5] associated with finite-size scaling analysis of liquid-solid coexistence at fixed T * using cell models indicates that the estimate of the pressure for N = 256 differs by 4%-6% from the N = ∞ value.…”
mentioning
confidence: 99%
“…The likely explanation for this discrepancy is the highly compressible nature of the gas phase. Recently, Nayhouse et al [1][2][3][4][5][6][7] proposed a series of simple and efficient direct and indirect simulation techniques for accurate simulation of fluid-solid coexistence. These approaches are based on extensions or generalizations of the constrained cell model 8,9 description of the solid phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation